2010
DOI: 10.1186/1472-6963-10-259
|View full text |Cite
|
Sign up to set email alerts
|

"Done more for me in a fortnight than anybody done in all me life." How welfare rights advice can help people with cancer

Abstract: BackgroundIn the UK many people with cancer and their carers do not have easy access to the welfare benefits to which they are entitled adding further strain to the process of dealing with cancer. It is estimated that nine out of ten cancer patients' households experience loss of income as a direct result of cancer, which, due to its socio-economic patterning disproportionately affects those most likely to be financially disadvantaged. In the UK proactive welfare rights advice services accessed via health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 23 publications
0
52
0
1
Order By: Relevance
“…In contrast to the lack of quantitative evidence regarding direct physical health benefits, some qualitative data showed that recipients perceived that their physical health improved as a result of receiving additional income (for example, Clarke et al. 2001, Greasley 2003, Borland & Owens 2004, Greasley & Small 2005a,b, Moffatt et al. 2006a, 2010, Doncaster 2008, Moffatt & Scambler 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the lack of quantitative evidence regarding direct physical health benefits, some qualitative data showed that recipients perceived that their physical health improved as a result of receiving additional income (for example, Clarke et al. 2001, Greasley 2003, Borland & Owens 2004, Greasley & Small 2005a,b, Moffatt et al. 2006a, 2010, Doncaster 2008, Moffatt & Scambler 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for direct non-medical costs have been found to include costs generated from travel and parking, increased household bills, new clothing, healthier food, household-and childcare-related services, fitness classes, relocation, house modifications and family and friends (Amir, Wilson, Hennings, & Young, 2012;Céilleachair et al, 2012;Longo, Fitch, Grignon, & McAndrew, 2016;McGrath, 2016b;Moffatt, Noble, & Exley, 2010;Timmons, Gooberman-Hill, & Sharp, 2013b). Knowledge of the expected costs is crucial for cancer patients to reduce their financial distress (Peppercorn, 2014) because experiencing a higher than expected financial burden has been found to increase experiences of financial distress (Chino et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Advice has been identified as vital in supporting health and disability benefit claimants to navigate their way through the benefit system (Shefer et al 2016;Barnes et al 2017). Advice that supports the uptake of welfare benefit entitlements can have a positive impact on mental and physical health (Corden et al 2010), may address health inequalities (Greig et al 2014), and can ease financial stresses in times of severe illness (Moffatt et al 2010). This advice is often given by advice-providing charities to people who would not otherwise be able to afford to access legal advice.…”
Section: Welfare Reform and Advice Services In The Ukmentioning
confidence: 99%